Neopestalotiopsis hadrolaeliae sp. nov., a new endophytic species from the roots of the endangered orchid Hadrolaelia jongheana in Brazil - Freitas, Emiliane F. S.; Da Silva, Meiriele; Barros, Marcos V. P.; Kasuya, Maria C. M. (Phytotaxa, 2019)
A new endophytic fungal species, Neopestalotiopsis hadrolaeliae, is described from roots of Hadrolaelia jongheana, an endangered orchid species growing in Brazil. Multigene phylogenetic analyses coupled with morphological observations facilitated the identification of new species isolated from the roots of Hadrolaelia jongheana. Phylogenetic analyses based on ITS, TUB and TEF DNA sequences showed that the new taxon is different from reported Neopestalotiopsis species. Descriptions and illustrations and notes are provided for the new species, which we name herein as Neopestalotiopsis hadrolaeliae.